2012
DOI: 10.1177/009102601204100303
|View full text |Cite
|
Sign up to set email alerts
|

Leisure Ethic, Money Ethic, and Occupational Commitment among Recreation and Park Professionals: Does Gender Make a Difference?

Abstract: We developed a model and investigated the relationship between (1) leisure ethic, money ethic and (2) occupational commitment. We collected data from 397 professionals in the public sector using a stratified random sample of National Recreation and Park Association (NRPA) professionals in the USA. Results suggested that females had high leisure ethic, low money ethic, and low continuance commitment. Career tenure was associated with high leisure ethic and all three components of commitment. After controlling f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 53 publications
0
15
0
Order By: Relevance
“…This pattern for affective OC corresponds to existing meta-analytical evidence (Lee et al, 2000), which has pointed to a nonsignificant (r = .01, based on a k of 11) and highly heterogeneous marriage-affective OC relationship (i.e., 41.27% of the variance between effect sizes were accounted for by artifacts). Regarding normative OC, one article found a nonsignificant correlation of r = .01 (Cunningham et al, 2012), whereas another found a positive correlation of r = .11 (Yuan and Li, 2012). For continuance OC, the only identified correlation was r = .12 (Cunningham et al, 2012).…”
Section: Results: Life Role As Spouse and Occupational Commitmentmentioning
confidence: 93%
See 1 more Smart Citation
“…This pattern for affective OC corresponds to existing meta-analytical evidence (Lee et al, 2000), which has pointed to a nonsignificant (r = .01, based on a k of 11) and highly heterogeneous marriage-affective OC relationship (i.e., 41.27% of the variance between effect sizes were accounted for by artifacts). Regarding normative OC, one article found a nonsignificant correlation of r = .01 (Cunningham et al, 2012), whereas another found a positive correlation of r = .11 (Yuan and Li, 2012). For continuance OC, the only identified correlation was r = .12 (Cunningham et al, 2012).…”
Section: Results: Life Role As Spouse and Occupational Commitmentmentioning
confidence: 93%
“…Regarding normative OC, one article found a nonsignificant correlation of r = .01 (Cunningham et al, 2012), whereas another found a positive correlation of r = .11 (Yuan and Li, 2012). For continuance OC, the only identified correlation was r = .12 (Cunningham et al, 2012). Worth mentioning, Wallace (1997)-who already disparaged that studies on side-bet factors, such as marriage, fail to measure continuance OC-found no association between marriage and continuance OC within a multiple regression analysis.…”
Section: Results: Life Role As Spouse and Occupational Commitmentmentioning
confidence: 99%
“…In the literature review, it is understood that there were many individual, organizational and professional antecedents of occupational commitment (Meyer and Espinoza, 2016). Age (Benligiray, and Sönmez, 2013;Meyer et al, 1993;Parasuraman and Nachman, 1987), gender (Cunningham et al, 2012;Snape, et al, 2008), ethic (Özer and Uyar, 2010), experience, occupational tenure, seniority (Benligiray, and Sönmez, 2013;Tang et al, 2012;Ozmen et al, 2005;Meyer et al, 1993), educational status (Benligiray, and Sonmez, 2013;Cohen, 2007), stress (Aydin, 2010), perceived occupational image (Lim, et al, 2000), organizational commitment (Cohen, 2007), motivation (Lauermann et al, 2017), job satisfaction (Lu, et al, 2002;Kaldenberg et al, 1995;Tak and Çiftçioğlu, 2008), pay satisfaction, work-itself satisfaction, supervision satisfaction, co-workers satisfaction, promotion opportunities satisfaction (Shamina, 2014) and burnout (Raiziene and Endriulaitiene, 2007) are some of the antecedents of occupational commitment. In addition, occupational commitment is positively related to productivity, motivation (Güleryüz et al, 2008;Jauch et al, 1978), job satisfaction, organizational commitment (Blau, 2000;Lee, et al, 2000), commitment to work, commitment to family (Benligiray and Sönmez, 2011), organizational citizenship behavior (Aledeinat et al, 2017;Aslan, 2008) and life satisfaction (Özdevecioğlu and Aktaş, 2007).…”
Section: Occupational Commitmentmentioning
confidence: 99%
“…Based on the attachment theory, employees "tend to have a natural tendency to build and maintain durable bonds of affection with familiar, irreplaceable organisations" (Sable, 2008). Although it is believed that OC is important to both individuals as well asorganisations (Cunningham et al, 2012) as it curbs deviant workplace behaviour and it promotes positive outcomes such as productivity and acceptance of organisational goals and values (Brett et al, 1995;Judge et al, 1999;Tang and Chiu 2003);researchers have not yet agreed on a common definition of organisational commitment as the only common view is on its belonging tothe social exchange theory (Aruștei,2013). This theory was originally developed by Blau (1964) who tried to explain there a sons behind the emergence of employees' attitudes and behaviours that are not enforced through a formal contract.…”
Section: 2organisational Commitmentmentioning
confidence: 99%